2013
DOI: 10.1097/psy.0b013e318276cb0d
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electrical Myocardial Remodeling in a Rodent Model of Depression

Abstract: Intermittent social stress procedure is associated with depression-like symptoms and altered myocardial electrical stability in a potentially proarrhythmic manner. In particular, reduced myocardial refractoriness and impaired conduction, which are considered major determinants of arrhythmogenesis, represent possible mechanisms underlying cardiac vulnerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 25 publications
2
33
0
Order By: Relevance
“…Many clinical studies have suggested that depression is an independent risk of VA and sudden cardiac death [22], [23], and animal experiments have shown a link between depression and increased vulnerability to arrhythmias [24], [25]. Therefore, we hypothesized that depression would exacerbate the electrical instability and increase the onset of VA in a post-infarcted heart.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Many clinical studies have suggested that depression is an independent risk of VA and sudden cardiac death [22], [23], and animal experiments have shown a link between depression and increased vulnerability to arrhythmias [24], [25]. Therefore, we hypothesized that depression would exacerbate the electrical instability and increase the onset of VA in a post-infarcted heart.…”
Section: Discussionmentioning
confidence: 97%
“…A previous meta-analysis suggested that post-MI depression is associated with a 1.6- to 2.7-fold increased risk of impaired cardiovascular outcomes within 24 months [5]. Depression is associated with abnormal cardiac electrophysiology features, such as prolonged QT duration and low heart rate variability [6], and significantly increases the risk of ventricular arrhythmia (VA) and sudden cardiac death (SCD) [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…This stress involves placement of a rodent into the cage of an aggressive “resident” conspecific that will attack the intruder (Koolhaas et al, 1997). Repeated resident-intruder stress results in HPA dysfunction, decreased social interaction, anxiety-like behaviors, anhedonia, self-administration of drugs of abuse and decreased heart rate variability, alterations in circadian rhythm amplitudes and long lasting pro-arrhythmic effects (Carnevali et al, 2013b; Miczek et al, 2004; Rygula et al, 2005; Tornatzky and Miczek, 1994; Wood et al, 2012; Wood et al, 2010). Substantial individual variability exists in the consequences of resident-intruder stress.…”
Section: Stress Coping Strategy and Individual Differences In Stress mentioning
confidence: 99%
“…In the study by Verrier et al (344) discussed above, cardiac fibrillatory threshold potentials were reduced by 40% in stressed dogs. A more recent experiment in stressed rodents also reported decreased effective refractory periods, an impaired conduction of electrical activities, and ventricular fibrosis (50). Autonomic imbalance and catecholamine surges are implicated in the arrhythmogenic effects of emotional disturbance, as shown by Lampert et al (189,190) who reported that increases in catecholamine levels during human emotional turmoil are correlated with changes in heart rate, systolic blood pressure, and repolarization indexes (T-wave amplitude, T-wave area, and T-wave alternans, which is a periodic beat-to-beat variation in the amplitude or shape of the ECG and is an indicator of those at high risk of developing potentially fatal cardiac arrhythmias).…”
Section: Stress-induced Cardiac Ischemia and Arrhythmiasmentioning
confidence: 99%
“…Interestingly, the intensity of the cardiac autonomic response is related to the degree of the emotional perturbation (302). The social defeat test can also induce a proarrhythmogenic state in the myocardium, possibly through diminishing myocardial refractoriness and impaired conduction (50).…”
Section: Animal Models Of Physical Stressmentioning
confidence: 99%